PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPRITUAL DAN MOTIVASI TERHADAP KINERJA GURU MADRASAH ALIYAH NEGERI 1 MALANG - Haryati Haryati; Hadi Sunaryo; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT  This study aims to determine the emotional intelligence, spiritual intelligence and motivation on the performance of madrasah teachersAliyah Negeri 1 Malang.ThisresearchisExplanatory Research research. Emotional intelligence research data, spiritual intelligence and work motivation on the performance of madrasah teachers of thepoorcountry. Population in this research is all teacher of Madrasah Aliyah Negeri 1 Malang. Data collection using questionnaires and documentation.Data analysis using testinstrument, normalitytest, multiple linear regression analysis, classical assumption, hypothesis test. Based on theresults of this study can beconcluded that moral intelligencedoes not affectthe performance of teachers, spiritual intelligence significantly affec tthe performance of Madrasah Aliyah Negeri 1 Malang teachers. Keywords:Emotional Intelligence, Spiritual Intelligence And Motivation.